Juridical Study of Trading Halt at IDX During Significant Decline of the Composite Stock Price Index (IHSG) - Eijileen, Brigitta Kezia; Antunez, Carla Xelena; Kusuma, Katya Aiko; Deru, Kesya Chantall Alisya (Anthology: Inside Intellectual Property Rights, 2025)
The Composite Stock Price Index (IHSG) declining sharply in early 2025 shows the importance of having a lower point in Indonesia’s capital market which affects a lot of factors including investors, issuers, regulators, and even the national economy. This journal has analyzed calamity for the capital market alongside the reason why the capital markets face a downturn. The capital markets which are under the jurisdiction of Law No.8/1995 and No.40/2007 are tasked with fostering deep financial intermediation for business and government activities, and public investment. The head of the OJK with the stock exchange industry setting the rules in the governance of IDX, places strong edges around, within, and in the capital market giving a protection to the investment climate. The safeguard guarantees that events in March and April 2025 show how far compliance with regulation goes but stretches beyond that to issues of market confidence and trust. Response from both the government and relevant authorities included extreme steps, such as instating trading suspensions, to stem panic selling and create some level of time out. These measures, while on some level unavoidable, highlighted the need for communication and harmonization among the regulators, market agents, and the public.